O papel das crenças na violência conjugal e impactos na saúde mental - Lemos, Dayse Chaves (Universidade do Vale do Rio dos Sinos, 2025)
The aim of this dissertation was to analyze the role of beliefs about intimate partner violence in the occurrence of violence and its impacts on mental health. This dissertation is composed of three empirical articles. The first qualitative and exploratory study aimed to investigate beliefs about intimate partner violence through a focus group. The results revealed three central axes of beliefs: 1) the influence of culture, gender, and masculinity on the acceptance of violence; 2) transgenerationality and the naturalization of violence; and 3) justifications for the occurrence of violence. The second quantitative study aimed to identify the level of agreement with these beliefs, compare the perspectives of men and women, and verify which sociodemographic characteristics could predict higher levels of agreement with the beliefs. The results showed low levels of agreement with beliefs legitimizing violence, but men presented higher levels of agreement with these beliefs than women (p<0.05). The third study, of a correlational nature, sought to analyze the level of agreement with the beliefs and verify possible associations with perpetration and victimization in relationships and their impact on mental health. The results showed low levels of agreement with the beliefs, but high rates of violence and an association between the occurrence of intimate partner violence and mental illness. The dissertation findings reveal an initial scenario of transformation in beliefs about violence, which still does not seem to be reflected in changes in violent behavior in intimate relationships
Keywords: Violência conjugal; Crenças; Saúde mental; Intimate partner violence; Beliefs; Mental health; ACCNPQ::Ciências Humanas::Psicologia